Net-Loss Reciprocation and the Context Dependency of Economic Choices - Clemens König (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2013)
This paper proposes a novel explanation for the context dependency of individual choices in two-player games. Context dependency refers to the well-established phenomenon that a player, when choosing from a given opportunity set created by the other player's strategy, chooses differently in different situations because of different alternatives to the other player's strategy. The utility model used to explain this kind of context dependency incorporates a preference for net-loss reciprocation. Net-loss reciprocation means that a player's willingness to impose a net loss (i.e., loss minus gain) on the other player increases in the net loss that he or she derives from the other player's strategy. I show that net-loss reciprocation together with the method for calculating net losses developed in this paper explains the context dependencies in individual behaviour that have been documented in a number of experimental studies, whereas existing models of intention-based reciprocity fail to explain all the evidence.
urn:nbn:de:bvb:19-epub-17474-2
Keywords: C70; C91; D63; D64; 330; Reciprocity; Fairness; Experimental economics; Game theory; Loss aversion